Nondestructive hole doping enabled photocurrent enhancement of layered tungsten diselenide. (28th February 2019) - Lei, Bo; Zheng, Yue; Hu, Zehua; Guo, Rui; Xiang, Du; Liu, Tao; Wang, Yanan; Lai, Min; He, Jun; Chen, Wei
Abstract: Atomically thin tungsten diselenide (WSe2 ) has emerged as a promising material for the next generation electronic and optoelectronic devices. Here, we report an enhancement of WSe2 photodetector performance via surface functionalization with molybdenum trioxide (MoO3 ). Strong hole doping from MoO3 to WSe2 was revealed by in situ field-effect transistor device evaluation, x-ray photoelectron spectroscopy and ultraviolet photoelectron spectroscopy measurements. Moreover, the responsivity and external quantum efficiency of WSe2 photodetector increased around eight folders after the surface functionalization with MoO3 . We attribute the enhanced performance to the narrowed Schottky barrier and the modulation of the trap states by surface functionalization.